Implementation Environmental Education with 2013 Curiculum of Early Cildhood Education (Study Descriptive in PAUD Taman Belia Candi Semarang 2016-2017) - Astriayulita, Alinna (BELIA: Early Childhood Education Papers, 2017)
The provision of environmental education can be provided in accordance with the competencies in the 2013 curriculum of core competencies number 3 and 4 which can not be separated from each other as they are interconnected, containing knowledge and skills that can provide environmental education. Children have the skills and knowledge in the form of skills in solving  problems, especially problems in the environment. This research uses qualitative method with descriptive research type in early childhood of Taman Belia Candi Semarang. Data collection in this study includes observation, interview and documentation. Interview with headmaster, head of curriculum, all central teachers and students from kindergarten class A student of Taman Belia Candi Semarang City. Environmental Education. Provision of environmental education in early childhood of Taman Belia Candi is given indirectly and activities. There are several factors that support and hinder the provision of environmental education. Supporting factors are; Improved curriculum, clean and healthy living habits, provision of hygiene aids, good communication with parents, and out-of-school visits for strengthening knowledge. Inhibiting factors include; Changing child responsiveness and lack of teacher and parent collaboration to develop the curriculum.